Are Antimicrobial Peptide Dendrimers an Escape from ESKAPE? - Kawano, Yayoi (Adv Wound Care (New Rochelle), 2020)
Significance: The crisis of antimicrobial resistance (AMR) increases dramatically despite all efforts to use available antibiotics or last resort antimicrobial agents. The spread of the AMR, declared as one of the most important health-related issues, warrants the development of new antimicrobial strategies. Recent Advances: Antimicrobial peptides (AMPs) and AMP dendrimers (AMPDs), as well as polymer dendrimers are relatively new and promising strategies with the potential to overcome drug resistance issues arising in ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) colonizing chronic wounds. Critical Issues: AMPs–AMPDs suffer from limited efficacy, short-lasting bioactivity, and concerns of toxicity. To circumvent these drawbacks, their covalent coupling to biopolymers and/or encapsulation into different drug carrier systems is investigated, with a special focus on topical applications. Future Directions: Scientists and the pharmaceutical industry should focus on this challenging subject to either improve the activity of existing antimicrobial agents or find new drug candidates. The focus should be put on the discovery of new drugs or the combination of existing drugs for a better synergy, taking into account all kinds of wounds and existing pathogens, and more specifically on the development of next-generation antimicrobial peptides, encompassing the delivery carrier toward improved pharmacokinetics and efficacy.